Pediococcus pentosaceus JS35 improved flavor, metabolic profile of fermentation supernatant of mulberry leaf powder and increased its antioxidant capacity - Meng, Caiyan; Wang, Yutong; Xie, Jiawen; Xuan, Jiajia; Geng, Jingze; Liu, Guanhui; Tu, Jie; Xiao, Hang (Frontiers in Nutrition, 2025)
Pediococcus pentosaceus JS35 was used to improve flavor, metabolic profile and antioxidant activity of mulberry leaf powder. Gas chromatography ion mobility spectrometry (GC-IMS) analysis revealed that fermentation increased the contents of floral and fruity flavor compounds such as dihydrolinalool and 2-phenylethanol, while decreased the grassy, pungent odor compounds. Non-targeted metabolomics analysis showed that Pediococcus pentosaceus JS35 altered the metabolic profile of mulberry leaf, especially increased the content of flavonoids metabolites such as kaempferol, quercetin and daidzein. Compared with the unfermented sample, the fermented supernatant had higher antioxidant capacity in vitro and in Caenorhabditis elegans. Furthermore, the fermented supernatant supplementation significantly prolonged the lifespan of Caenorhabditis elegans. In conclusion, fermentation by Pediococcus pentosaceus JS35 improved the flavor and active compounds of mulberry leaf, and the fermented product had effective antioxidant capacity. This study will provide ideas for the application of Pediococcus pentosaceus JS35 and the processing of mulberry leaf into functional foods or food ingredient.